Conservation and diversity of Palaearctic grasslands – Editorial to the 5th EDGG special issue in Hacquetia - Valkó, Orsolya; Labadessa, Rocco; Palpurina, Salza; Burrascano, Sabina; Ushimaru, Atushi; Venn, Stephen (Hacquetia, 2019)
Palaearctic grasslands are diverse and dynamic ecosystems that are in the focus of ecology, conservation biology and agronomy. This special issue is dedicated to the biodiversity and conservation issues of Palaearctic grasslands and was initiated by the Eurasian Dry Grassland Group members attending the 14th Eurasian Dry Grassland Conference (EDGC) at Sulmona, Italy in 2018. The papers in this special issue cover a wide range of grassland ecosystems from mountain dry grasslands to lowland loess grasslands, feathergrass steppes and wet grasslands, and focus on the biodiversity values and conservation issues of Palaearctic grasslands. We believe that this compilation will contribute to a better understanding of the ecology of grasslands and support their more effective conservation.